Do fans impact sports outcomes? A COVID-19 natural experiment - Cross, J.; Uhrig, R. (SSRN, 2020)
This paper studies the effect of fan attendance on home field advantage in top European soccer leagues. We exploit exogenous variation in the level of fan attendance driven by COVID-19 mitigation policies and find that the home field advantage, as measured by home goals minus away goals, is reduced by 57% across the English Premier League, German Bundesliga, Italian Serie A, and Spanish La Liga. We find that this leads to a shift in match outcomes from wins to losses with no change in the probability that a match is a draw.